A CPW-Fed Circular Wide-Slot UWB Antenna with Wide Tunable and Flexible Reconfigurable Dual Notch Bands - Yingsong Li; Wenxing Li; Qiubo Ye (The Scientific World Journal)
A coplanar waveguide (CPW)-fed circular slot antenna with wide tunable dual band-notched function and frequency reconfigurable characteristic is designed, and its performance is verified experimentally for ultra-wideband (UWB) communication applications. The dual band-notched function is achieved by using a T-shaped stepped impedance resonator (T-SIR) inserted inside the circular ring radiation patch and by etching a parallel stub loaded resonator (PSLR) in the CPW transmission line, while the wide tunable bands can be implemented by adjusting the dimensions of the T-SIR and the PSLR. The notch band reconfigurable characteristic is realized by integrating three switches into the T-SIR and the PSLR. The numerical and experimental results show that the proposed antenna has a wide bandwidth ranging from 2.7 GHz to 12 GHz with voltage standing wave ratio (VSWR) less than 2, except for the two notch bands operating at 3.8–5.9 GHz and 7.7–9.2 GHz, respectively. In addition, the proposed antenna has been optimized to a compact size and can provide omnidirectional radiation patterns, which are suitable for UWB communication applications.